2016
DOI: 10.7196/sajcc.2016.v32i2.253
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to implementing evidence-based practice in a private intensive care unit in the Eastern Cape

Abstract: Background. Evidence-based practices (EBPs) have been promoted to enhance the delivery of patient care, reduce cost, increase patient and family satisfaction and contribute to professional development. Individual and organisational barriers can hamper the implementation of EBP, which can be detrimental to healthcare delivery. Objective. To determine the individual and organisational implementation barriers of EBP among nurses in a private intensive care unit (ICU). Methods. A quantitative research design was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 22 publications
2
56
2
Order By: Relevance
“…A major barrier identified in this study was insufficient knowledge. These findings were consistent with those from other studies, which identified insufficient knowledge as main barrier to the uptake of EBP (Jordan et al., ; Kin et al., ; Koehn & Lehmen, ; Mallion & Brooke, ; McInerney & Suleman, ; Underhill et al., ; Wang, Jiang, Wang, Wang, & Bai, ). Another barrier to EBP that has been commonly identified in research studies is the perception of insufficient power to adjust patient care processes.…”
Section: Literature Reviewsupporting
confidence: 92%
See 2 more Smart Citations
“…A major barrier identified in this study was insufficient knowledge. These findings were consistent with those from other studies, which identified insufficient knowledge as main barrier to the uptake of EBP (Jordan et al., ; Kin et al., ; Koehn & Lehmen, ; Mallion & Brooke, ; McInerney & Suleman, ; Underhill et al., ; Wang, Jiang, Wang, Wang, & Bai, ). Another barrier to EBP that has been commonly identified in research studies is the perception of insufficient power to adjust patient care processes.…”
Section: Literature Reviewsupporting
confidence: 92%
“…A review of the literature revealed that nurses from different countries and settings have consistently complained of experiencing similar barriers to the adoption of EBP, which include lack of time , perception of insufficient power to adjust patient care processes, inadequate organisational support, insufficient access to research journals and articles and insufficient knowledge and skills (Baird & Miller, ; Carroll et al., ; Funk et al., ; Gerrish & Cooke, ; Jordan, Bowers, & Morton, ; Kin et al., ; Mallion & Brooke, ; Mehrdad et al., ; Underhill, Roper, Siefert, Boucher, & Berry, ). In one study, Funk et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the 16 studies ( n = 15) focused entirely on EBP, specifically perceptions, knowledge, and barriers (Amini, Taghiloo, Bagheri, Fallah, & Ramazani Badr, ; Ay, Gençtürk, & Turan Miral, ; DeBruyn et al., ; Duncombe, ; Ebrahimi, Seyedrasooli, Khodadadi, & Yousefi, ; Farokhzadian et al., ; Hweidi, Tawalbeh, Al‐Hassan, Alayadeh, & Al‐Smadi, ; Jordan, Bowers, & Morton, ; Kahouei, Alaei, Shariat Panahi, & Zadeh, ; Karki et al., ; Khammarnia, Haj Mohammadi, Amani, Rezaeian, & Setoodehzadeh, ; Mehrdad, Salsali, & Kazemnejad, ; Naderkhah et al., ; Subramaniam, Krishinan, Thandapani, Van Rostenberghe, & Berahim, ; Yava et al., ). It is unlikely that studies did not report on outcomes (barriers to EBP among nurses) since most of the studies included nurses as the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies employed qualitative research methods (Adib‐Hajbaghery, ; DeBruyn et al., ). The nurses included in the studies were from diverse settings such as nurse researchers, educators, and graduate students (DeBruyn et al., ); psychiatric, geriatric, hospital, and community settings (Duncombe, ; Ebrahimi et al., ); critical care units (Hweidi et al., ; Jordan et al., ); and teaching hospitals (Ay et al., ; Khammarnia et al., ).…”
Section: Resultsmentioning
confidence: 99%